Analysis of Students’ Mathematical Creative Thinking Skills in Solving Multicultural-Based Open-Ended Problems - Azizatun Nafi'ah; Arezqi Tunggal Asmana; Abdur Rohim (Jurnal Inovasi Pendidikan Matematika (JIPM), 2026)
This study aims to examine students’ mathematical creative thinking skills and the factors influencing their ability to solve multicultural-based open-ended problems. Data were collected through three open-ended mathematical creative thinking test items and interviews with the participants. The data analysis process was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the mathematical creative thinking skills of the first subject (S1) and the third subject (S3) were categorized as creative, while the second subject (S2) was categorized as less creative. Subjects S1 and S3 successfully fulfilled all indicators of creative thinking, namely fluency, flexibility, originality, and elaboration, whereas subject S2 only fulfilled the indicators of fluency and elaboration.